Characterisation of the Structure and Properties of Liquid-Liquid Interfaces Using Computer Simulations - Byrne, Emily Hannah (Curtin University, 2020)
Soft interfaces play a fundamental role in many biological and industrial processes. In this work, atomistic simulations were used to study the structural properties of the interfaces between water and five organic solvents, with special attention devoted to the 1,2-dichloroethane-water system. This system is widely used in sensing applications currently in development, and was used as a prototypical case to study the effect of ions on interfacial structure and to gain insight into their transfer mechanism.